2020
DOI: 10.1038/s41598-020-61677-w
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of glycine receptor single-channel conductance by intracellular phosphorylation

Abstract: Glycine receptors (GlyRs) are anion-permeable pentameric ligand-gated ion channels (pLGICs). The GlyR activation is critical for the control of key neurophysiological functions, such as motor coordination, respiratory control, muscle tone and pain processing. The relevance of the GlyR function is further highlighted by the presence of abnormal glycinergic inhibition in many pathophysiological states, such as hyperekplexia, epilepsy, autism and chronic pain. In this context, previous studies have shown that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 62 publications
0
27
1
Order By: Relevance
“…Thus, the present results support a predominant presence of the 1 subunit in the VTA, but not in the PFC. Although, phosphorylation and receptor density can affect some physiological characteristic of GlyRs (Taleb and Betz, 1994;Moraga-Cid et al, 2020) and might explain some of the distinct properties found in VTA and PFC neurons, we believe that these differences are related to differences on subunit expression as discussed previously. This is further supported by the sensitivity of GlyRs to ethanol in the 1 KI and 2 KO mice summarized in table 1.…”
Section: Glyrs Subunits Can Be Differentiated By Their Electrophysiological and Pharmacological Propertiesmentioning
confidence: 73%
“…Thus, the present results support a predominant presence of the 1 subunit in the VTA, but not in the PFC. Although, phosphorylation and receptor density can affect some physiological characteristic of GlyRs (Taleb and Betz, 1994;Moraga-Cid et al, 2020) and might explain some of the distinct properties found in VTA and PFC neurons, we believe that these differences are related to differences on subunit expression as discussed previously. This is further supported by the sensitivity of GlyRs to ethanol in the 1 KI and 2 KO mice summarized in table 1.…”
Section: Glyrs Subunits Can Be Differentiated By Their Electrophysiological and Pharmacological Propertiesmentioning
confidence: 73%
“…The large intracellular loop of the inhibitory GlyR contains numerous motifs for intracellular interaction [2] , [4] , [17] , [18] , [42] , [43] , [44] , [45] and modulation of receptor function [7] , [17] , [34] , [46] , [47] . Here, we investigated the function of a proline-rich motif, 365 PPPAPSKSP 373 , which forms a PPII helix that is located in the intracellular TM3-4 loop of the human GlyRα1 subunit.…”
Section: Discussionmentioning
confidence: 99%
“…We further showed that the values are increased by channel dephosphorylation induced by CaMKII inhibition or by intracellular ATP removal. In a similar way, the single-channel conductances of ligand-gated glycine receptors, glutamate receptors, and 5-HT3 receptors are modulated by phosphorylation (54)(55)(56).…”
Section: Discussionmentioning
confidence: 99%